2018
DOI: 10.1111/zph.12529
|View full text |Cite
|
Sign up to set email alerts
|

A repeated cross‐sectional study of the epidemiology of Campylobacter and antimicrobial resistant Enterobacteriaceae in free‐living Canada geese in Guelph, Ontario, Canada

Abstract: From May through October 2016, we conducted a repeated cross‐sectional study examining the effects of temporal, spatial, flock and demographic factors (i.e. juvenile vs. adult) on the prevalence of Campylobacter and antimicrobial resistant Enterobacteriaceae among 344 fresh faecal samples collected from Canada geese (Branta canadensis) from four locations where birds nested in Guelph, Ontario, Canada. The overall prevalence of Campylobacter among all fresh faecal samples was 9.3% and was greatest in the fall w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our results are in line with a recent study demonstrating the existence of certain sub lineages of ST-45 forming genetically isolated clades containing C. jejuni strains with extremely similar genomes regardless of time and location of sampling [27]. In addition to the highly mobile nature of many wild bird species to disseminate bacteria in the environment [32], the World Health Organization in 2017 (World Health Organization, 2017) showed that many of these microorganisms exhibited resistance to antimicrobials considered of highest importance to human medicine [37,38]. Interestingly, C.jejuni strains isolated in this study showed a moderate percentage resistance to tetracycline, to ciprofloxacin and nalidixic acid, suggesting that the antimicrobial resistance could be acquired by horizontal gene transfer [39] or, to the usage antibiotics as a therapeutic agent in dairy cattle and poultry farms [40].…”
Section: Discussionsupporting
confidence: 77%
“…Our results are in line with a recent study demonstrating the existence of certain sub lineages of ST-45 forming genetically isolated clades containing C. jejuni strains with extremely similar genomes regardless of time and location of sampling [27]. In addition to the highly mobile nature of many wild bird species to disseminate bacteria in the environment [32], the World Health Organization in 2017 (World Health Organization, 2017) showed that many of these microorganisms exhibited resistance to antimicrobials considered of highest importance to human medicine [37,38]. Interestingly, C.jejuni strains isolated in this study showed a moderate percentage resistance to tetracycline, to ciprofloxacin and nalidixic acid, suggesting that the antimicrobial resistance could be acquired by horizontal gene transfer [39] or, to the usage antibiotics as a therapeutic agent in dairy cattle and poultry farms [40].…”
Section: Discussionsupporting
confidence: 77%
“…Repeat cross-sectional studies performed across multiple seasons, while holding the methods and location(s) fixed, allow for broader generalizability in comparison with data obtained from birds in a single or limited number of seasons. Given the evidence of seasonal variation in the carriage of a number of pathogenic organisms by wild birds (Campylobacter, Salmonella, and E. coli and associated AMR; Girdwood et al, 1985;Morabito et al, 2001;Broman et al, 2002;Kirk et al, 2002;Colles et al, 2009;Hughes et al, 2009;Hald et al, 2016;Vogt et al, 2018Vogt et al, , 2019, it may be problematic to compare prevalence estimates from studies which sampled birds in different seasons. Data from repeat cross-sectional studies that represent multiple seasons may be of use in assessing the Animal Health Research Reviews seasonality of the carriage of certain microorganisms and can thereby support or undermine the comparability of certain prevalence estimates from different seasons.…”
Section: Methodsmentioning
confidence: 99%
“…Of the sample of articles discussed in this subsection, a small number of studies reported how isolates with intermediate susceptibility were handled. Two studies retained such isolates as intermediates (Shobrak and Abo-Amer, 2014;Vidal et al, 2017), another reclassified the isolates as susceptible (Pinto et al, 2015), and in our previous work we classified all intermediates as resistant (Vogt et al, 2018(Vogt et al, , 2019. Recognition of the various factors that influence MDR definitions has resulted in recent efforts to develop a standard definition of MDR that is internationally recognized, in order to facilitate comparisons between studies (Magiorakos et al, 2012).…”
Section: Defining Prevalence Outcomes and Prevalence Estimate Parametersmentioning
confidence: 99%
See 2 more Smart Citations